(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Spinal tuberculosis is a specific inflammation of the vertebrae and discs caused by tuberculosis bacilli, accounting for about 1-2% of tuberculosis patients. Symptoms of spinal tuberculosis include pain, spinal deformity and signs of nerve compression. Objectives: 1. Review the imaging characteristics of patients with lumbar spinal tuberculosis undergoing pedicle screws fixation at the National Lung Hospital; 2. Compare the level of pain before and after pedicle screws fixation in patients with lumbar spine tuberculosis. Method: Retrospective descriptive study. Results: The patients had severe spinal injuries on diagnostic imaging, including: Paravertebral abscess (100% of patients), spinal instability (100% of patients); kyphoscoliosis (93.2% of patients), spinal stenosis (79.6% of patients), epidural abscess (63.6% of patients). Patientshad preoperative hight pain scores with average VAS score: 7.35 ± 2.27 points, of which 4 patients (9%) had mild pain, 25 patients had moderate pain (56.9%), 15 Patients with severe pain (34.1%). After surgery, the patient’s pain level decreased significantly with an average VAS score of 3.22 ± 2.15 points, of which 18 patients (41%) had no pain, 22 patients (50%) had mild pain. 4 patients (9%) had moderate pain. Conclusion: Pedicle screws fixation surgery in the treatment of lumbar spine tuberculosis has a significant pain-relieving effect. However, it only addresses cases of spinal pain due to instability. For radicular pain due to nerve compression, combined nerve decompression surgery is needed to completely resolve the damage caused by spinal tuberculosis.